2013
DOI: 10.1371/journal.pone.0060616
|View full text |Cite
|
Sign up to set email alerts
|

Do Contaminants Originating from State-of-the-Art Treated Wastewater Impact the Ecological Quality of Surface Waters?

Abstract: Since the 1980s, advances in wastewater treatment technology have led to considerably improved surface water quality in the urban areas of many high income countries. However, trace concentrations of organic wastewater-associated contaminants may still pose a key environmental hazard impairing the ecological quality of surface waters. To identify key impact factors, we analyzed the effects of a wide range of anthropogenic and environmental variables on the aquatic macroinvertebrate community. We assessed ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 50 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…While the differences in organismal responses to mixtures of MPs among species still remain largely to be discovered, altered species composition in natural populations close to waste water treatment plants suggest radical differences in tolerance to MP mixtures among species (e.g. Englert, Zubrod, Schulz, & Bundschuh, ; Münze et al., ; Stalter, Magdeburg, Quednow, Botzat, & Oehlmann, ). Gastropods, for example, may be relatively tolerant to pesticides, while similar concentrations experienced by other, more sensitive species may have detrimental effects on survival and population size (Hua & Relyea, ).…”
Section: Discussionmentioning
confidence: 99%
“…While the differences in organismal responses to mixtures of MPs among species still remain largely to be discovered, altered species composition in natural populations close to waste water treatment plants suggest radical differences in tolerance to MP mixtures among species (e.g. Englert, Zubrod, Schulz, & Bundschuh, ; Münze et al., ; Stalter, Magdeburg, Quednow, Botzat, & Oehlmann, ). Gastropods, for example, may be relatively tolerant to pesticides, while similar concentrations experienced by other, more sensitive species may have detrimental effects on survival and population size (Hua & Relyea, ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings matched the results of Stalter et al . (), who found that the use of percentile values did not enhance the strength of correlation between macroinvertebrate communities and several organic contaminants.…”
Section: Discussionmentioning
confidence: 98%
“…Further, Ellis (1995) reports that statistical analysis of invertebrate population densities in rivers impacted by urban wastewater discharges reveals a numerical dominance of oligochaetes and low species diversity downstream of combined sewer outfall sites, suggesting that this phenomenon is associated with both physical disturbance due to high turbulent flows and acute toxicity suppressing pollution-sensitive species. A study by Stalter et al (2013) also revealed that even wastewater effluents discharged by Bstate-of-the-art^wastewater treatment facilities also impact the ecological quality of receiving surface water bodies. Their findings revealed two important factors contributing to pollution-mediated invertebrate mortality and reduced species diversity.…”
Section: Invertebratesmentioning
confidence: 99%